Inventário de exemplares arquitetônicos em madeira no município de Chapada/RS: patrimônios de valor arquitetônico, histórico e cultural - Andrade, Amanda Schirmer de (2019)
The present dissertation aimed to analyze wood buildings in the municipality of Chapada / RS, both in architectural and aesthetic aspects, thus being able to compare the thirteen buildings researched in their many characteristics and components, which led to partially understand how people built having possession of this material and popular knowledge. Valuing the assets that still survive in contemporary times, whether material or immaterial, strengthens the relationship between the community and the good. Real estate material assets, today, are the most recognized forms of heritage goods, both for their visibility and their use, as they are part of people's daily lives. In order to catalog the goods, inventory registration forms were used. For the selection of goods, the criterion used was the existence of some architectural singularity, regardless of the area or element that had it. A bibliographical review was carried out about the themes involved (heritage, architecture, immigration, wood and the municipality), field research on buildings, photographic survey, subsequent measurement and redesign of the selected sites for analysis and interpretation between assets. All this so that it was possible to find out how the elements and characteristics were treated by families, without considering the end use of the place. Thus, seeking to deliver the results to the community, an educational brochure was developed to be delivered simultaneously to the photographic exhibition called “Olhares da Arquitetura”, which takes place in an itinerant way, composed of eleven enlarged photos to be inaugurated in Santa Maria, in the Gama d'Eça Educational Museum in 2019, as well as a story published in a local newspaper.